PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN VAKSINASI COVID-19 TAHUN 2021 STUDI KASUS DESA AURSATI KECAMATAN TAMBANG KABUPATEN KAMPAR - Dewi Juliana; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study was to determine the effect of public perception of covid-19 and the benefits of covid-19 vaccine on the people of Aur Sati village, Tambang District, Kampar regency. This research has used quantitative research methods. Data collection was carried out using a questionnaire with a sample of 100 people from villages in Tambang District, Kampar Regency. The data were processed by multiple linear regression analysis using the SPSS 23 program. this research has used Frederick’s theory. policy of a series of actions of activities proposed by a person, group or government in a particular environment where there are obstacles and opportunities to the implementation of the proposed policy in order to achieve certain objectives. The results of the study found that respondents' assumptions about public perceptions of COVID-19 were the first majority, 69% of respondents agreed with the belief that Covid-19 disease is contagious. The second majority of 59% of respondents believe that Covid-19 exists. It can be concluded that residents in Aur Sati have a perception that the Covid-19 disease exists. Respondents' assumptions about citizens' perceptions of the benefits of the Covid-19 vaccine are the first majority, 71% of respondents said they agreed with the government's support for providing Covid-19 vaccines in stages. The second majority, 70% of respondents believe that the government's program to administer the Covid-19 vaccine supports the health of the masses. it can be concluded that Aur Sari residents have the perception that they agree with the government's vaccination policy. meanwhile, the results of statistical tests show that there is an influence on citizens ' perceptions of covid-19 and the benefits of covid-19 vaccines on covid-19 vaccine policies with the implementation of covid-19 vaccination policies. Keywords: Public Perception, Benefits of Vaccines, and Covid-19 Vaccine Policy